2014
DOI: 10.1115/1.4027276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Load on Close-Coupled Post-Injection Efficacy for Soot Reduction in an Optical Heavy-Duty Diesel Research Engine

Abstract: A s s is ta n t P ro fe sso r M e c h a n ic a l and N uclear E n g in e e rin g D epartm ent, C enter fo r C o m b u s tio n , P ow er and P ro p u ls io n , P e n nsylva nia State U nive rsity, 111 R esearch East B u ild in g , U n iv e rs ity Park, PA 1 6 8 0 2 e -m a il: jx o 2 2 @ e n g r.p s u .e d u M a rk M usculusT e ch n ica l S taff E n g in e C o m b u s tio n D epartm ent, C o m b u s tio n Research F a cility, S andia N ational Lab o ra to rie s, P.O. B ox 969 , M S 9 05 3 , L iv e rm o re , C A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Many studies have been carried out on the reduction in soot emission from diesel engines by close-coupled post injection, in which a small amount of fuel is injected during the combustion of main sprays . Among them, several studies have demonstrated the sootreduction effects of post injection and investigated the soot-reduction mechanisms for heavy-duty diesel engines [15][16][17][18][19][20][21]. For example, O'Connor and Musculus [18] performed experiments using a heavy-duty (HD) optical diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out on the reduction in soot emission from diesel engines by close-coupled post injection, in which a small amount of fuel is injected during the combustion of main sprays . Among them, several studies have demonstrated the sootreduction effects of post injection and investigated the soot-reduction mechanisms for heavy-duty diesel engines [15][16][17][18][19][20][21]. For example, O'Connor and Musculus [18] performed experiments using a heavy-duty (HD) optical diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as dividing the main single injection profile in two or more injection pulses with definite delay dwell between the injections [12]. Post-injection, which refers to the small amount of fuel (typically up to approximately 20% of total fuel) [13] injected for a short time after the main injection, is one of the effective multiple injection strategies used to reduce in-cylinder soot emission [14,15].…”
Section: Introductionmentioning
confidence: 99%